Analysis of the tourism suitability index and development strategy for Telok Berdiri Mangrove Ecotourism in Sungai Kupah Village, Kubu Raya Regency - Dewi Nur Khayani; Widadi Padmarsari Soetignya; Fitra Wira Hadinata (Universitas Malikussaleh, 2026)
Mangrove ecotourism in Telok Berdiri, Sungai Kupah Village, Kubu Raya Regency, is a mangrove-based tourism area with considerable ecological, educational, and economic potential. However, its development is still constrained by limited supporting facilities and insufficient tourism promotion. This study aimed to assess the suitability of the area for mangrove ecotourism development and to formulate appropriate development strategies. A descriptive research method with a qualitative approach was employed. Data were collected through field observations, interviews, and measurements of mangrove biophysical parameters at three observation stations. The data were analyzed using the Tourism Suitability Index (TSI) and SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. The results showed that Station 1 obtained a TSI value of 2.35 and was classified as suitable for mangrove ecotourism development. In contrast, Stations 2 and 3 obtained TSI values of 1.37 and 1.22, respectively, and were classified as unsuitable. The SWOT analysis indicated that the recommended development strategies include strengthening community-based education and conservation programs, improving tourism facilities and promotional activities, and conducting regular monitoring and evaluation. Therefore, Telok Berdiri Mangrove Ecotourism has the potential to be developed sustainably through management practices that integrate environmental, social, and economic aspects of the local community. Keywords: Mangrove Ecotourism; SWOT Analysis; Sungai Kupah; Telok Berdiri; Tourism Suitability Index